Decrease in CD4 and CD8 lymphocytes are predictors of severe clinical picture and unfavorable outcome of the disease in patients with COVID-19 - Jovičić Biljana Popovska; Raković Ivana; Đorđević Nemanja; Gavrilović Jagoda; Čanović Predrag; Marjanović Ružica Radojević; Petrović Sara; Milosavljević Katarina B.; Divjak Ana; Stanković Nenad; Paunović Milan; Milosavljević Miloš Z. (Open Medicine, 2025)
The main objective of this study was to investigate the association between CD4+ and CD8+ lymphocyte values and disease severity, need for oxygen therapy and disease outcomes.